Faithful Silencing: The Rejection of Loudspeakers as Islamic Piety in West Java, Indonesia - Asep Muhamad Iqbal; Irma Riyani (IAIN Palangka Raya, 2025)
The phenomenon of non-use of technology remains relatively underexplored. In West Java, certain religious communities choose not to use specific technologies, particularly within the Islamic anti-speaker group known as the Aspek (anti-speaker) community. This study aims to analyze the piety of Muslim members of the Aspek community in rejecting the use of loudspeaker technology. Data were collected through fieldwork, including unstructured interviews with leaders and members of the Aspek community, as well as direct observation. The data were analyzed using the multilevel model of resistance to information technology implementation as the theoretical framework. The findings reveal that the Aspek community’s rejection of loudspeakers is influenced by user-related factors, particularly religious beliefs and interpretations, as well as technology-related factors. These two aspects shape a form of communal technological non-use deeply rooted in cultural and spiritual values.